Disiplin Kerja Sebagai Pemediasi Pengaruh Motivasi Dan Dukungan Rekan Kerja Terhadap Kinerja Karyawan - Kukuh Harianto; Rike Kusuma Wardhani; Heru Sutapa (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
This research analyzes work discipline as a mediator of the influence of motivation and co-worker support on employee performance. The sample used in this research was 35 employees of UD WilisManikam Kediri. The main type of data used in this research is primary data collected in a questionnaire and processed using the SPSS version 26 application. The results obtained in this research are that motivation and support from colleagues have a positive and significant effect on employee work discipline. Then the variables of motivation, co-worker support and work discipline each directly have a positive and significant effect on employee performance. Apart from that, the work discipline variable cannot mediate the influence of motivation on employee performance, but the work discipline variable can mediate the influence of co-worker support on employee performance.